Complex Regional Pain Syndrome After Herpes Zoster: A Case Report - Fulya Bakılan; Sibel Ösken; Ayşe Ekim (Galenos Yayinevi, 2018)
A 78-year-old male patient, diagnosed with herpes zoster infection, had color change, stiffness, swelling and burning pain on his left hand. Hand joints were painful, joint range of motion decreased and hyperpigmented, macular lesions on the left C5-C6 dermatome region was determined. After the medical and physical therapy programme, symptoms decreased significantly. Complex regional pain syndrome (CRPS) is a painful disorder with swelling, stiffness in joints, vascular instability, and dystrophic skin changes. Symptoms most commonly occur after trauma, stroke, surgery, myocardial infarction, fracture, cancer. In this case, an unusual cause of complex regional pain syndrome, herpes zoster, was reported. Only a few cases have been reported to date. In this case report, it is emphasized that CRPS can occur as a complication of many conditions. Early diagnosis and appropriate treatment lead to better outcomes.